Prawda w gazetach rękopiśmiennych z 2. połowy XVIII wieku (na wybranym materiale). Rekonesans badawczy = The truth in handwritten newspapers of the second half of the 18th century (on the selected material). Research reconnaissance - Bizior, Renata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In this article, I discuss the issue of truth in relation to selected handwritten newspapers from the second half of the 18th century. The discussion is preceded by the characteristics of the communication phenomenon of newspapers written in the 18th century. The paper presents the meaning of truth as an important category influencing the informational value of press releases and newspapers as well as for their organization (structure and macrostructure).
Keywords: prawda; gazety rękopiśmienne; wiadomość prasowa; gatunek wypowiedzi; modalność epistemiczna; Kitowicz, Jędrzej (1728-1804); truth; handwritten newspapers; genre; press release; epistemic modality; 18 w.